Macrocyclic complexes containing a platinacycle or palladacycle composed of an isocyanate dimer unit: Reactivity towards isocyanides and cyclotrimerization of isocyanates. (15th October 2016) - Choi, Jun-Hwan; Jung, Kang-Yeoun; Kim, Yong-Joo; Im, Hye Jin; Lee, Soon W.
Graphical abstract: Upon treatment with sulfur, bis(phosphine) mononuclear Pd(II) and Pt(II) complexes containing an isocyanate dimer unit are converted to new macrocyclic complexes with four metallacycles. Abstract: The reactions of [Pt(styrene)(PMe3 )2 ] with 2 equiv. of alkyl or aryl isocyanate affored five-membered platinacycles, cis -[Pt{–N(R)C(O)N(R)C(O)–}(PMe3 )2 ] (R = CH2 C6 H5, p-ClC6 H4, p-OMeC6 H4 ). These complexes are the first examples of platinacycles containing an isocyanate dimer unit. When the five-membered bis(phosphine) platinacycles or palladacycles were treated with 2 equiv. of elemental sulfur, 16-membered cyclic products as an assembly of four platinacycles or palladacycles, [M(PR3 ){–N(R)C(O)N(R)C(O)–}]4, were readily obtained. These cyclic tetramers were cleaved using tert -butyl isocyanide (CN– t butyl, 4 equiv.), affording the corresponding monomeric complexes, [M(PR3 )(CN– t butyl){–N(R)C(O)N(R)C(O)–}] (M = Pt, Pd). An unusual cyclotrimerization of organic isocyanates catalyzed by zerovalent Pt complexes or five-membered platinacycles was observed. In addition, the direct cyclotrimerization of alkyl or aryl isocyanates using dialkyl Pt(II) or Pd(II) complexes was investigated. The cross cyclotrimerization of an aryl isocyanate and its derivative using a zerovalent Pd complex was also investigated.